Molecular Mechanisms Driving and Regulating the AAA+ ATPase VCP/p97, an Important Therapeutic Target for Treating Cancer, Neurological and Infectious Diseases - Sepideh Valimehr; Ashish Sethi; Manjari Shukla; Sudipta Bhattacharyya; Mohsen Kazemi; Isabelle Rouiller (Biomolecules, 2023)
p97/VCP, a highly conserved type II ATPase associated with diverse cellular activities (AAA+ ATPase), is an important therapeutic target in the treatment of neurodegenerative diseases and cancer. p97 performs a variety of functions in the cell and facilitates virus replication. It is a mechanochemical enzyme that generates mechanical force from ATP-binding and hydrolysis to perform several functions, including unfolding of protein substrates. Several dozens of cofactors/adaptors interact with p97 and define the multifunctionality of p97. This review presents the current understanding of the molecular mechanism of p97 during the ATPase cycle and its regulation by cofactors and small-molecule inhibitors. We compare detailed structural information obtained in different nucleotide states in the presence and absence of substrates and inhibitors. We also review how pathogenic gain-of-function mutations modify the conformational changes of p97 during the ATPase cycle. Overall, the review highlights how the mechanistic knowledge of p97 helps in designing pathway-specific modulators and inhibitors.